Determinants Of Tax Compliance for Business Actors and Independent Workers in The Perspective of Theory of Planned Behavior and Theory of Fiscal Psychology - Betha Februari Khristy; Baridwan, Zaki; Khoiru Rusydi, Mohamad (The International Journal of Accounting and Business Society, 2022)
Purpose—This study aims to analyze determinants of tax compliance intentions and behaviour using constructs derived from the Theory of Planned Behavior, i.e., tax morale, social norms, detection risk, penalty magnitude, and tax complexity, and the Theory of Fiscal Psychology, i.e., perception about the government. Design/methodology/approach —This research was conducted on 120 business actors and independent workers in the Greater Malang region using a survey and partial Least Squares analysis performed in SmartPLS. Findings — This study finds that tax morale, social norms, penalty magnitude, tax complexity, and perception about the government and that tax compliance intention, detection risk, and penalty magnitude influence tax compliance behaviour to determine tax compliance intention. Furthermore, detection risk does not affect tax compliance intention, and tax complexity does not influence tax compliance behaviour. Practical implications —Based on the findings, the government is advised, through the Directorate General of Tax, to develop policies and approaches supporting tax morale, strengthen community bases to create tax-aware environments, maintain law enforcement through investigation and application of penalties, build an easy-to-reach taxation system, and create transparency to enhance taxpayer’s trust to the government that eventually leads to higher tax compliance intention and behaviour. Originality/value—The findings support the inclusion of the Theory of Fiscal Psychology in the development of the Theory of Planned Behavior to explain tax compliance behaviour and provide a new perspective that, in the context of tax compliance, not all aspects of perceived behavioural control have the same effect on both behavioural intention and produced behaviour. Keywords — Tax compliance behaviour; Theory of Planned Behavior; Theory of Fiscal Psychology. Paper type — Positive paradigm